Nursing Care for Outpatients Receiving Treatment for Chronic Venous Insufficiency by Wearing Compression Stocking - Leelatanon, Aphanan; Jaroensuk, Pinyo (Journal of Health Sciences and Wellness, 2024)
Chronic venous insuffciency (CVI) refers to a dysfunction of venous system. The condition is characterized by symptoms like tired legs, heaviness, pain after prolonged standing or sitting, edema, and skin changes, which may develop into chronic leg ulcers. The risk of CVI increases with age, sex - especially in females, obesity, regular prolonged periods standing or sitting at work, pregnancy, family history of varicose veins, deep vein thrombosis (DVT), hypertension, constipation, and previous leg injury. A proper diagnosis for CVI is duplex ultrasound. Treatment for CVI is by wearing compression stockings, by medication, sclerotherapy, and operations. Compression stocking is a standard treatment for CVl with high safety. It can assist in improving venous return, musculoskeletal pump function, and reduce edema in lower extremities. The nursing process for patients who receive treatment by wearing compression stocking is composed of 5 steps - assessment, diagnosis, planning, implementation, and evaluation. The objective is to provide patients with knowledge and understanding, so that they receive stockings with the appropriate size and level, and are able to wear compression stockings according to the most effective treatment plan.